Revealed meta-preferences : axiomatic foundations of normative assessments in the capability approach - Silva-Leander, S (Oxford Poverty & Human Development Initiative (OPHI), 2011)
This paper explores the possibility of defining a non-utilitarian normative standard for assessments of welfare and deprivation. The paper contributes to this end in three ways. First, the paper formalises a key aspect of Prof. Sen’s critique of neoclassical welfare economics, regarding the assumption of consistent utility-maximisation in the revealed preference theory. Secondly, the paper explores alternative formulations of the axiom of revealed preferences that are consistent with Prof. Sen’s critique and proposes a set of intuitive assumptions to characterise the relation between observed choices and underlying preferences in the absence of consistent utility-maximisation. Finally, we use these to construct two alternative normative ranking rules that can be used in empirical applications of Prof. Sen’s so-called capability approach.